KEPERIDIAN DAN RASIO SEKS KETURUNAN KUMBANG AMBROSIA XYLEBORUS FERRUGINEUS YANG DIPELIHARA PADA MEDIA SERBUK LIMA JENIS KAYU1) - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Ambrosia beetle Xvleborus ferrugineus (Coleoptera: Scolytidae) was reared on sawdust based artificial media of five wood species, i.e. bireh(Betula sp.),. elm (Ulmus americana), jack pine (Pinus sp.), oak (Quercus sp.), and an unknown species. Each sawdust media was prepared in capped test tubes and one female beetle per tube was then introduced. The culture media were incubated in a dark room at 28°C and 70% RH for 40 days.The result showed that the most fecund cultures, by mean of 25.9 and 24.0 progenies per tube, were respectively produced by the beetles reared on the elm and unknown sawdust diets. The moderate fecundity, producing 15.6 and 14.2 progenies per tube, was respectively yielded on the oak and birch media, and the less fecund one, 9.4 progenies each tube, was that on the jack pine sawdust diet. The female beetle reared on the entire diets yielded progenies with a spanan- droua sex ratios ranging from 18.B to 24.1 females per one male. There is no dignificant difference among the progeny's sex ratios produced by the beetle reared on the various culture media.